Development of Finger Puppet Media for Receptive Language Ability in Children Aged 4-5 Years at PAUD Puspa Kencana - Nurlela Azizah; Eka Mei Ratnasari (Jurnal Caksana : Pendidikan Anak Usia Dini, 2026)
Receptive language ability in early childhood is a crucial aspect of development that supports communication skills, social interaction, and children's learning readiness at subsequent educational levels. Based on preliminary observations at PAUD Puspa Kencana, Central Lampung, it was found that some children in Group A, aged 4–5 years, still experience difficulties in understanding simple instructions, listening to stories, and retelling the content of lessons. This condition is influenced by the limited learning media used by teachers, resulting in a less engaging learning process that has not optimally stimulated receptive language abilities. This study aims to develop finger puppet media and test its feasibility and effectiveness in improving receptive language skills in early childhood. The research employed the Research and Development (R&D) method using a simplified Borg and Gall model consisting of seven stages: potential and problem identification, data collection, product design, design validation, design revision, product testing, and final product. The research subjects consisted of 18 children from Group A and one classroom teacher. Data collection techniques included observation, interviews, documentation, and expert validation sheets. The results showed that the finger puppet media obtained a material expert validation percentage of 87.5%, a media expert validation of 97.5%, and an instrument validation of 96%, all in the highly feasible category. Product trials demonstrated an improvement in children's ability to listen, understand stories, and respond actively to learning. The novelty of this research lies in the development of family-themed finger puppet media based on Islamic values that are contextual to children's lives.